The Effect of Audiovisual Media for Prenatal Yoga on Knowledge and Prenatal Yoga Activities of Pregnant Women - Maulania Bulan Maghfiroh; Lilik Indahwati; Diah Royani Meisani; Safrina Dewi Ratnaningrum; Herdhika Ayu Retno Kusumasari (Jurnal Kebidanan, 2025)
Background: Pregnant women are at risk of various health problems during pregnancy and childbirth. Prenatal yoga is a recommended physical activity that supports labor preparation and can be practiced independently with proper guidance. Audiovisual media are more interactive and effective in increasing knowledge and promoting behavioral change. Objective: This study aimed to investigate the impact of audiovisual media on pregnant women’s knowledge and practices regarding prenatal yoga. Methods: This pre-experimental study used a one-group pretest–posttest design with a cross-sectional approach. The sample consisted of 50 pregnant women in Malang City selected through purposive sampling. Data was collected using questionnaires and analyzed with the Wilcoxon Signed Rank Test. Results: The findings showed a significant improvement in both knowledge and practice after the intervention. The analysis revealed p-values of 0.000 (p < 0.05) for knowledge and 0.014 (p < 0.05) for practice, indicating that audiovisual media effectively enhanced participants’ understanding and engagement in prenatal yoga. Conclusion: Audiovisual media significantly improve pregnant women’s knowledge and participation in prenatal yoga. This method can be used by health workers as an effective educational tool to motivate expectant mothers to practice prenatal yoga regularly for better pregnancy outcomes.